Biodegradation of MC252 polycyclic aromatic hydrocarbons and alkanes in two coastal wetlands. (August 2020) - Rodrigue, Matthew; Elango, Vijaikrishnah; Curtis, David; Collins, Autumn W.; Pardue, John H.
Abstract: Complementary microbial and geochemical assessment techniques investigated the biodegradation of PAHs and alkanes in salt marshes impacted by crude oil following the Macondo spill. Contamination was observed in the top 10 cm of the marsh profile based on PAH analysis and measurement of the δ 13 C signature of impacted marsh soils. Measurement of evolution of 13 C depleted CO2 indicated mineralization of crude oil ranging from 2.7–12.1 mg CO2 -C/m 2 -hr. Changes in weathering ratios of alkylated phenanthrenes and dibenzothiophenes indicated loss of these 3-ring PAHs consistent with biodegradation. A diverse microbial population was observed at both locations dominated by Gammaproteobacteria and including known hydrocarbon degraders such as Marinobacter and Alcanivorax . There was shared richness between sites and across seasons but results suggested substantial turnover of phylotypes in space and time. Biodegradation of alkanes and alkylated PAHs occurred when oxygen was provided in laboratory reactors but not in the absence of oxygen. Graphical abstract: Unlabelled Image Highlights: δ 13 C signature of evolved CO2 reflects ongoing salt marsh crude oil mineralization. Changes in PAH weathering ratios over time in coastal marshes reflect biodegradation. Oiled marsh microbial populations are dynamic, yet consistently dominated by Gammaproteobacteria . Oxygen stimulates PAH and alkane biodegradation in oiled marsh soils. Porewater nutrient profiles show significant internal sources of N and P for biodegradation.